Typologie žen a mužů v českých reklamách - Srpová, Hana (Stylistyka, 2008)
The article deals with the different types of women and men in the Czech advertisements. The author starts from the premise that in order to increase the effectiveness of advertising, it is essential for advertisers to select suitable means of expression primarily on the basis of the needs or weaknesses of the target group (the segment of the population at which the product is mainly aimed, i.e. the group which is required to start buying the product), and in verbal terms, on the particular sociolect of the target group. The author’s research leads her to claim that it is actually the target group that plays the decisive role in the selection of advertising strategies. Women and men are not only target groups, but also useful models for visual and audiovisual advertising. The way in which people are used in advertising greatly reflects the stereotypes current in a particular society and at a particular time. In this sense advertising acts as a mirror of society - of its behaviours, value system, systems of relationships, and moral principles. The author analyses individual cases in which advertisers depict women and men. She classifies various types of women and men used in Czech mass media advertising, noting the verbal means, which differ depending on the target group.